Anthropogenic Light, Noise, and Vegetation Cover Differentially Impact Different Foraging Guilds of Bat on an Opencast Mine in South Africa - Cory-Toussaint, Dawn; Taylor, Peter J. (Frontiers in Ecology and Evolution, 2022)
Bats are known to be sensitive to changes in their environment. The impact of natural vegetation cover, artificial light intensity and noise (dBA) were investigated on the bat community on the opencast Venetia diamond mine using mixed-effects models. Clutter-feeding bats were virtually absent compared to surrounding natural habitats, suggesting the negative impact of vegetation removal and/or light and/or noise pollution. Mixed-effect models revealed that natural vegetation was the most important factor impacting species richness and overall bat activity. In general, bat activity of both open-air and clutter-edge foragers was negatively impacted over areas close to mining operations that were devoid of vegetation cover. Artificial light only significantly affected feeding activity with less feeding activity in the lit areas. Anthropogenic noise had no significant impact on bat activity and species richness. Our study highlights the importance of vegetation cover and the complexity of the interaction between bats and the environment incorporating anthropogenic factors (artificial lighting, continuous noise, and habitat degradation) and natural factors such as minimum temperature, moon phase, and season that confound trends in bat species richness and responses in relation to opencast mining.